IRRATIONAL FACTORS AFFECTING THE PURCHASE INTENTION OF VIRTUAL GOODS IN FIRST-PERSON SHOOTER ONLINE GAMES - Adhi Darmawan Supriadi; Daniel Tumpal H. Aruan (Sean Institute, 2023)
The purchase intent of in-game items in online games has attracted the attention of a number of studies. Most studies are based on volitional factors. This study investigated the determinants of purchase intent of virtual goods items in FPS online games with volitional and non-volitional factors. The online survey was conducted among 107 CS:GO, Apex Legends, Valorant, or PUBG: BATTLEGROUNDS players. Structural equation modeling (SEM) from the data collected shows that volitional factors, non-volitional factors, and game-related items influence the intention to buy game items on FPS online games.